Characterization of the Avian Pathogenic Escherichia coli Hemagglutinin Tsh, a Member of the Immunoglobulin A Protease-Type Family of Autotransporters - Stathopoulos, Christos (American Society for Microbiology, 1999)
We reported earlier that a single gene, tsh, isolated from a strain of avian pathogenic Escherichia coli (APEC) was sufficient to confer on E. coli K-12 a hemagglutinin-positive phenotype and that the deduced sequence of the Tsh protein shared homology to the serine-type immunoglobulin A (IgA) proteases of Neisseria gonorrhoeae and Haemophilus influenzae. In this report we show that E. coli K-12 containing the recombinant tsh gene produced two proteins, a 106-kDa extracellular protein and a 33-kDa outer membrane protein, and was also able to agglutinate chicken erythrocytes. N-terminal sequence data indicated that the 106-kDa protein, designated Tsh(s), was derived from the N-terminal end of Tsh after the removal of a 52-amino-acid N-terminal signal peptide, while the 33-kDa protein, designated Tsh(β), was derived from the C-terminal end of Tsh starting at residue N(1101). The Tsh(s) domain contains the 7-amino-acid serine protease motif that includes the active-site serine (S(259)), found also in the secreted domains of the IgA proteases. However, site-directed mutagenesis of S(259) did not abolish the hemagglutinin activity or the extracellular secretion of Tsh(s) indicating that host-directed proteolysis was mediating the release of Tsh(s). Studies with an E. coli K-12 ompT mutant strain showed that the surface protease OmpT was not needed for the secretion of Tsh(s). Tsh belongs to a subclass of the IgA protease family, which also includes EspC of enteropathogenic E. coli, EspP of enterohemorragic E. coli, and SepA and VirG of Shigella flexneri, which seem to involve a host endopeptidase to achieve extracellular release of their N-terminal domains. In proteolytic studies conducted in vitro, Tsh(s) did not cleave the substrate of the IgA proteases, human IgA1 or chicken IgA, and did not show proteolytic activity in a casein-based assay. Correlation of Tsh expression and hemagglutination activity appears to be a very complex phenomenon, influenced by strain and environmental conditions. Nevertheless, for both APEC and recombinant E. coli K-12 strains containing the tsh gene, it was only the whole bacterial cells and not the cell-free supernatants that could confer hemagglutinin activity. Our results provide insights into the expression, secretion, and proteolytic features of the Tsh protein, which belongs to the growing family of gram-negative bacterial extracellular virulence factors, named autotransporters, which utilize a self-mediated mechanism to achieve export across the bacterial cell envelope.